An analytical method for predicting mode-I crack propagation process and resistance curve of rock and concrete materials. (April 2019) - Wang, Hong-Wei; Wu, Zhi-Min; Wang, Yan-Jie; Yu, Rena C.
Highlights: The method can analytically predict the crack growth process of rock and concrete. Given fundamental materials parameters, the load-displacement curve can be predicted. There is no complicated iterative operation involved in the calculating progress. The analytical results show good agreement with the experimental results. The closure effect by the cohesive force on calculated results are discussed. Abstract: In this paper, taking into account the fictitious crack model and the closure effect of the crack opening displacement (COD) induced by the cohesive force, an analytical method with the crack mouth opening displacement (CMOD) as the control parameter is proposed to predict the mode-I crack propagation process of rock and concrete materials by using stress intensity factor (SIF)-based criteria. With this method, the load-crack mouth opening displacement ( P -CMOD) curve, crack extension resistance curve ( K R -curve), and fracture process zone (FPZ) length during crack propagation are analytically obtained. The validity of the proposed analytical method is then verified with the experimental results of three-point bending tests on rock and concrete beams. Therefore, given the tensile strength f t, Young's modulus E, initial fracture toughness K I C ini, and fracture energy G F, the complete mode-I crack propagation process of rock and concrete beams under three-point bending can be predicted accurately using the proposed analytical method without iteration in calculating the cohesive stress. Finally, the influence of the closure effect of the COD induced by the cohesive force on the P -CMOD curve, K R -curve, and FPZ length is discussed. The results show that although ignoring the closure effect of the COD induced by the cohesive force has little effect on the shape of the P -CMOD curve, the value of crack extension resistance and the maximum FPZ length are significantly underestimated, and the calculation error increases with the crack propagation and then decreases gradually when the FPZ length reaches the maximum.